PERAN MAHASISWA TEOLOGI SEBAGAI PELAYAN TUHAN DALAM MEMAHAMI TEKNOLOGI INFORMASI DAN KOMUNIKASI DI ERA REVOLUSI INDUSTRI 4.0 - Kurnia Sumartha Taileleu (Jurnal Matetes STT Ebenhaezer, 2021)
Abstrack The world is currently experiencing demands for change because of the Industrial Revolution 4.0, even this influence cannot be prevented by the role of theology students as servants of God in conveying the truth of God's word. This journal discusses the role of theology students as God's servants in understanding technology in the 4.0 era and does not rule out the possibility of conveying the truth of God's word. The method used in this journal is a qualitative method, namely completing data on the role of theology students as servants of God in understanding technology and conveying the truth of God's word. And the conclusion obtained is that the role of theology students as God's servants is to apply the method of conveying God's word with the technology that developed in the Industrial Revolution 4.0 AbstrakDunia sekarang ini mengalami tuntutan perubahan oleh karena Revolusi Indusri 4.0, bahkan pengaruh ini pun tidak dapat dihalangi peran mahasiswa teologi sebgai pelayan Tuhan dalam menyampaikan kebenaran firman Tuhan. Jurnal ini membahas mengenai peran mahasiswa teologi sebagai pelayan Tuhan dalam memahami teknologi di era 4.0 dan tak menutup kemungkinan dalam menyampaikan kebenaran firman Tuhan. Metode yang digunakan dalam jurnal ini ialah metode kualitatif yaitu merampungkan data-data mengenai peran mahasiswa teologi sebagai pelayan Tuhan dalam memahami teknologi dan menyampaikan kebenaran firman Tuhan. Dan kesimpulan yang diperoleh ialah peran mahasiswa teologia sebagai pelayan Tuhan ialah menerapkan cara menyampaikan firman Tuhan dengan teknologi yang berkembang di Revolusi Industri 4.0